Efficient access to a carbohydrate-derived 1,2,3-triazole linked to a flavonoid such as apigenin. A new entry to a potentially bioactive flavonoid hybrid - Mosset, Paul; Hamdi, Safwa; Kammoun, Majed (Synthesis)
Flavonoids are natural products which are present in many edible vegetables and fruits. They proved beneficial to health as they act as antioxidants and have showed many other interesting biological properties. However their poor bioavailability and fast metabolization led to a search of synthetic derivatives which remedy to these problems and improve the biological profile. In this context, a flavonoid-hybrid of apigeninin, known for its anticancer properties, was synthesized. Among the three phenolic hydroxyls of apigenin derivatized as acetates, the one in 7-position was selectively reacted by means of a deacetalization using imidazole in 1,4-dioxane. That enabled thereafter to graft a chain with a 1,2,3-triazole ring through a propargylation, removal of the remaining acetates by imidazole in methanol and finally by a “click reaction” with a 6-azido-saccharide derivative made from alpha-D-methylglucoside.